Effect of the Consonant–Vowel Structure of Written Words in Italian. Issue 5 (May 2014) - Chetail, Fabienne; Scaltritti, Michele; Content, Alain
Surprisingly little is known about the nature of intermediary sublexical units in visual word recognition in Italian, a language with a highly consistent print-to-sound mapping, which should enhance reliance on grapheme-to-phoneme correspondences. In the present study, we examined whether Italian readers are sensitive to large orthographic units defined by the consonant–vowel (CV) pattern of words and that do not directly map onto linguistic constituents. Participants had to judge the number of syllables in written words matched for the number of spoken syllables but comprising either one orthographic vowel cluster less than the number of syllables (hiatus words, e.g., tea tro ) or as many vowel clusters as syllables (e.g., a go sto ). Relative to control words, readers were slower and less accurate for hiatus words, for which they underestimated the number of syllables. This underestimation bias demonstrates that Italian readers are sensitive to large orthographic units stemming from a parsing process based on the CV pattern—that is, the arrangement of consonant and vowel letters.